Attribute based sanitizable signature scheme - Xi-meng LIU; Jian-feng MA; Jin-bo XIONG; Jun MA; Qi LI (Tongxin xuebao)
Sensitive information in the document needs to be hidden in cloud computing environment, and attribute based sanitizable signature (ABSS) scheme was proposed to solve this problem. The ABSS scheme brings the character of sanitiz-able into ABS in order to hide sensitive information, ensure signer's anonymity and achieve fine-grained access control. Un-der the CDH assumption, the ABSS scheme constructed was proved to be unforged in the standard model. Compared with existing schemes, the proposed ABSS scheme is more appropriate for cloud computing environment.